The application of digitalization technology in the the algerian television media. applied approach 2014 - Saad, Saad; Saidani, Salami (Social Empowerment Journal, 2020)
Modern technologies have imposed themselves on the audiovisual media industry and have become part of all its stages of production, distribution, transmission and reception, due to the technical, economic and application dimensions of this technology. Therefore, this intervention attempts to explain and explain the application of these technologies to the Algerian national public television, as it is the most powerful media organization in Algeria in2014